Properties of films obtained from biopolymers of different origins for skin lesions therapy - Bellini, Márcia Zilioli; Oliva Neto, Pedro de [UNESP]; Moraes, Ângela Maria (Instituto de Tecnologia do Paraná - Tecpar, 2015)
In this study, the effects of the origin of xanthan used, in combination with chitosan, to prepare films for the treatment of skin lesions were evaluated. The characteristics of the films obtained with xanthan commercially available for the food industry sector and xanthan originated from a fermentation process conducted in a pilot plant were compared. Results showed that the source did not strongly interfere in many of the properties of the films, such as the mechanical properties, cytotoxicity to L929 cells, absorption of simulated body fluid and culture medium, stability in water and saline solution. Hence, even though the properties of biopolymers of different sources might vary, the films prepared with two distinct types of xanthan gum could be considered as potentially safe and similar in terms of relevant characteristics considering the aimed application.
Keywords: Biomaterials; Biopolymers; Films; Membranes; Properties and Characterization; Biomedical applications